Spironolactone-Loaded LeciPlexes as Potential Topical Delivery Systems for Female Acne: In Vitro Appraisal and Ex Vivo Skin Permeability Studies - Ayman Salama; Mohamed Badran; Mohammed Elmowafy; Ghareb M. Soliman (MDPI AG, 2019)
Spironolactone (SP), an aldosterone antagonist with anti-androgen properties, has shown promising results in the treatment of female acne. However, its systemic side effects limit its clinical benefits. This study aimed to prepare and evaluate LeciPlexes for SP topical delivery. LeciPlexes were prepared by a one-step procedure and characterized using various techniques. Optimum LeciPlex preparation was incorporated into 1% methylcellulose gel and SP permeability was tested ex vivo in Sprague-Dawley rat skin. The maximum drug encapsulation efficiency obtained was 93.6 ± 6.9% and was dependent on the drug/phospholipid and surfactant/phospholipid ratios. A zeta potential of +49.3 ± 3.5 to +57.7 ± 3.3 mV and a size of 108 ± 25.3 to 668.5 ± 120.3 nm were observed for the LeciPlexes. FT-IR and DSC studies confirmed the incorporation of SP into the LeciPlexes through hydrophobic and hydrogen bonding interactions. SP release from the LeciPlex formulations was significantly slower than from the drug suspension. Cumulative SP permeated through rat skin from LeciPlex gel was about 2-fold higher than SP control gel. Cumulative SP deposited in the stratum corneum and other skin layers from the LeciPlex gel was about 1.8- and 2.6-fold higher than SP control gel, respectively. This new SP LeciPlex formulation is a promising carrier for the treatment of female acne.